Early Revelation of Leprosy in China by Sequential Antibody Analyses with LID-1 and PGL-I. (28th January 2013) - Qiong-Hua, Pan; Zhong-Yi, Zheng; Jun, Yang; Yan, Wen; Lian-Chao, Yuan; Huan-Ying, Li; Reed, Steven G.; Duthie, Malcolm S.
Abstract : Leprosy is a disabling chronic infection, with insidious onset that often evades early detection. In order to detect new leprosy cases in a timely manner, we conducted surveillance visits in some difficult-to-reach mountain areas in South West China where the disease is still prevalent. Our data confirm that Chinese multibacillary (MB) leprosy patients have strong antibody responses against Mycobacterium leprae antigens ND-O-BSA and LID-1. Contacts of clinically diagnosed patients were then monitored at regular intervals by both physical examinations and the laboratory determination of antibody responses in sera collected during these examinations. Elevations in antibody titers indicated the onset of MB leprosy in one of the contacts, and diagnosis was subsequently confirmed on physical examination. Our data indicate that rising antibody titers can be used as a trigger for physical examination or increased monitoring of particular individuals in order to provide early leprosy diagnosis.